Development of strength abilities of women taking into account the ovarian-menstrual cycle - Abramova, M. A.; Afanasenkova, N. V.; Sungurova, A. V.; Balyuk, V. G.; Mamontova, Yu. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to experimentally prove the effectiveness of the methodology for developing strength abilities in women, taking into account the ovarian-menstrual cycle.